The Effect of Throwing and Catching the Ball on the Social-Emotional Ability of 5-6-Year-Old Children in Smart Ceria Simbontar Kindergarten - Naibaho, Lusianna; Samosir, Rotua; Hulu, Adiani (Eximia, 2022)
This study aims to determine how much influence it has on the Social Emotional Ability of Children 5-6 Years Old in Smart Ceria Simbontar Kindergarten in the 2020/2021 Academic Year. The hypothesis is that Throwing and Catching the Ball has a positive and significant effect on the Social Emotional Ability of 5-6 Years Old Children in Smart Ceria Simbontar Kindergarten in Simbontar. This study uses a descriptive quantitative approach. The early childhood population in Smart Ceria Simbontar Kindergarten collects 30 people with a sample of 30 people. The data was collected using a closed questionnaire with as many as 30 items compiled by the author of variable indicators according to expert theory. The questionnaire trial was conducted on 30 early childhood children outside the study sample and has been tested for validation and reliability. The results of data analysis show that there is a positive and significant influence on the Ball Catching Influencer on Anal Socio-Emotional Ability Ages 5-6 Years in Smart Ceria Kindergarten in the 2020/2021 Academic Year with a coefficient of determination (r2) = 81.3% and a significant effect test is obtained (Fcount > Ftable of 54.77 > 4.17, meaning that H0 is rejected and H_ is accepted. This research is recommended to play-catch the ball in improving the social-emotional abilities of children aged 5-6 years in Smart Ceria Simbontar Kindergarten by the teacher must be carried out correctly.